"Moderate Effect of Achievement Moivaion on The Effect of Emotional Intelegence Level on Student Learning Outcomes in Economics (Survey in Class X IPS SMA Negeri Bandung Regency Southern Section of The Academic Year 2021/2022). - Yani Mulyani, - (2022)
This research is motivated by the fact that there are still many students who have learning outcomes that have not reached the Minimum Completeness Criteria (KKM) in economic subjects as seen from the results of the odd Semester Final Assessment (PAS) at the Southern Bandung Regency Senior High School for the 2021/2022 academic year. This study aims to determine the role of achievement motivation in moderating the influence of emotional intelligence on learning outcomes. The population in this study were high school students in Southern Bandung Regency with a total population of 959 people from five schools, using random sampling technique so that a sample of 283 students was obtained. The method used in this research is an explanatory survey, with technical data analysis using the MRA test or (Moderated Regression Analysis) with moderator variables. The results of this study indicate that: (i) General description of emotional intelligence, achievement motivation and learning outcomes are in the category. (ii) The level of emotional intelligence has an effect on learning outcomes in economic subjects. (iii) Achievement motivation has no effect on student learning outcomes in economic subjects. (vi) Achievement motivation weakens the influence of emotional intelligence on learning outcomes.